2023
DOI: 10.1002/sres.2942
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing sustainability performance of universities: A DMAIC approach

Abstract: This paper aims to assess and improve the sustainability performance at a higher educational institute (HEI) in UAE using DMAIC methodology, considering five sustainability aspects (knowledge, behaviour, concern, awareness and attitude). One primary and six secondary research questions were defined in the define phase. In the measure phase, a questionnaire was designed to measure the current sustainability level based on the five sustainability aspects. A questionnaire was distributed among campus populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Performance, which is also closely linked to sustainable development, is therefore influenced by many factors (from cluster 1, we can include innovations and strategies that follow governance and management directions, which are already part of cluster 2; in addition to governance and management, cluster 2 includes the frameworks needed for governance and management and hence strategies, and indicators that help managers to measure the achievements of the goals set in governance, management, and strategies). This is consistent with the findings of many authors who found that sustainability governance and strategic management (albeit facing many challenges) improved the sustainability performance [106][107][108], including in universities/higher education institutions [105].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Performance, which is also closely linked to sustainable development, is therefore influenced by many factors (from cluster 1, we can include innovations and strategies that follow governance and management directions, which are already part of cluster 2; in addition to governance and management, cluster 2 includes the frameworks needed for governance and management and hence strategies, and indicators that help managers to measure the achievements of the goals set in governance, management, and strategies). This is consistent with the findings of many authors who found that sustainability governance and strategic management (albeit facing many challenges) improved the sustainability performance [106][107][108], including in universities/higher education institutions [105].…”
Section: Discussionsupporting
confidence: 92%
“…In order to make the right decisions, key decision makers also need a relevant framework, and for this purpose, the authors developed a cybernetic model of the university's/HEI's transition to sustainability (see Figure 9). In order for a university/HEI to determine the level of sustainability it has achieved, it needs to develop an internal system of indicators that best reflect its specificities [105]. In Table 6, the authors propose some indicative indicators that universities/HEIs can use for this purpose.…”
Section: Discussionmentioning
confidence: 99%